Multifunctionalities enabled by the synergistic effects of mesoporous carbon dots and ZnO nanorods. (23rd November 2021) - Kavitha, T; Kumar, S
Abstract: In this study, CD/ZnO nanohybrids were synthesised by a simple, one-pot, cost-effective method and their structure and properties were investigated by physicochemical methods. The CD/ZnO nanohybrid exhibits excellent sunlight induced photocatalytic and antibacterial activity validating the development of remarkably efficient catalytic systems and effective bactericidal agents. The IV measurements of CD/ZnO nanohybrid shows over 12-fold increase in photocurrent compared to ZnO, opening pathways for the fabrication of efficient light harvesting system. Electrochemical property measurements demonstrate that CD/ZnO nanohybrid has large integral area of cyclic voltammetry loop, demonstrating their potential for supercapacitor applications. The study presents green chemistry strategy for the synthesis of CD/ZnO nanohybrids which exhibit multifunctionalities due to the synergy between CD and ZnO. The findings of the study demonstrate the potential of CD/ZnO nanohybrids for a multitude of energy and environmental solutions.